PROBLEMATIKA PROSES PEMBELAJARAN BAHASA INDONESIA SECARA DARING PADA MASA COVID 19 - Bambang Irawan (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
As it is today, the world has been confronted with a problem that occurs that is the epidemic of the corona virus, known as Coronavirus Disease 2019 (Covid-19). The Indonesian Government through the Minister of Education and Culture (Mendikbud), Nadiem Anwar Makariem, has issued a circular number 4 of 2020 concerning the Implementation of Education in the Coronavirus Disease Emergency Period (Covid-19). The circular contains several technical issues related to the learning process that must be carried out by the academic community. One such policy is to emphasize the academic community to carry out learning online (online) with the aim of preventing the spread of the covid-19 virus. This study aims to find out what are the problems of the online learning process in Indonesian during the 19th period in MA Darussalam and how is the solution of the problem. This research approach uses a qualitative research approach with data collection techniques by interviewing informants related to this research. Data analysis techniques used are domain and taxonomy analysis techniques. The results showed that the problematic of the process of learning Indonesian online is the lack of infrastructure such as students not carrying a cellphone, time constraints, difficulty evaluating, prone to cheating in doing assignments, difficult signal, and lack of understanding of student guardians. The solution to the problem is the need for stakeholder support to contribute to the success of the online learning process. These stakeholders include teachers, parents, students, schools and government.